The Role of Digital Transformation in Enhancing ESG Disclosure Practices in Saudi Companies - Almahuzi, Ahmed Salman; Alhamami, Mahdi Ahmed (International Review of Management and Marketing, 2026)
This study examines the role of digital transformation in enhancing environmental, social, and governance (ESG) disclosure practices in Saudi companies and its impact on investor confidence, focusing on improvements in transparency, timeliness, and completeness. The study adopted a quantitative approach, collecting data from professionals in finance, accounting, sustainability, and information technology in Saudi listed companies. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) to test the relationships among digital transformation, ESG disclosure quality, and investor confidence. The results show that digital transformation significantly improves ESG disclosure quality through advanced reporting systems and data-driven technologies. In turn, enhanced disclosure quality strengthens investor confidence by increasing credibility, trust, and investment willingness. The findings also confirm that ESG disclosure quality fully mediates the relationship between digital transformation and investor confidence. This study provides empirical evidence of the mediating role of ESG disclosure quality in linking digital transformation to investor confidence in an emerging market, offering insights for improving ESG reporting through digital technologies.